Smart Apps Creator as Digital Media in Arabic Language Learning - Ihda Auliya Ainul Jannah; Syarifudin Basyar; Erlina Erlina; Koderi Koderi; Nurul Fadlilahh (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar Pamekasan, 2026)
Arabic language learning in Islamic educational institutions continues to face challenges related to low student engagement and the limited use of interactive digital learning media. Although Smart Apps Creator (SAC) has been widely used to develop digital teaching materials, a comprehensive synthesis of its trends, effectiveness, and implementation challenges in Arabic language learning remains limited. This study aims to analyze research trends, identify advantages and limitations, and examine the effectiveness of SAC-based digital media in enhancing student motivation, engagement, and learning outcomes in Arabic language education. This study employs a literature review method by systematically collecting and analyzing relevant studies published between 2019 and 2024 from national and international academic databases. The findings indicate that SAC-based digital media are effective in increasing student motivation, engagement, and learning outcomes, particularly in reading, vocabulary, and writing skills. However, limitations are found in supporting speaking and listening skills, content personalization, teachers’ digital competence, and technological infrastructure in certain contexts. This study contributes by providing a structured synthesis of empirical findings and offering pedagogical and technological recommendations for optimizing the use of SAC in Arabic language learning, particularly in Islamic educational settings.